Influence of Some Alcohols on the Dissolution of Tin in Nitric Acid - Abdel Aal, A.; Elkot, A.M.; El-Sheikh, R.; Ghoza, A.M. (Asian Journal of Chemistry, 2010)
The behaviour of tin metal in nitric acid solutions was investigated using thermometric (Mylius) technique. Addition of alcohols to 4 M nitric acid showed a marked decrease in the dissolution rate as methanol < ethanol < propanol < butanol < isobutanol. The inhibition action is attributed to alcohols adsorption on the metal surface through –OH group. The alcohol adsorption follows Langmuier adsorption isotherm.